Interaction among SOX10, PAX3 and MITF, three genes altered in Waardenburg syndrome - Sock, Elisabeth; Wegner, Michael; et al. (Human Molecular Genetics, 2000)
Waardenburg syndrome (WS) is an autosomal dominant disorder with an incidence of 1 in 40 000 that manifests with sensorineural deafness and pigmentation defects. It is classified into four types depending on the presence or absence of additional symptoms. WS1 and WS3 are due to mutations in the PAX3 gene whereas some WS2 cases are associated with mutations in the microphthalmia-associated transcription factor (MITF) gene. The WS4 phenotype can result from mutations in the endothelin-B receptor gene (EDNRB), in the gene for its ligand, endothelin-3 (EDN3), or in the SOX10 gene. PAX3 has been shown to regulate MITF gene expression. The recent implication of SOX10 in WS4 prompted us to test whether this transcription factor, known to cooperate in vitro with PAX3, is also able to regulate expression from the MITF promoter. Here we show that SOX10, in synergy with PAX3, strongly activates MITF expression in transfection assays. Analyses revealed that PAX3 and SOX10 interact directly by binding to a proximal region of the MITF promoter containing binding sites for both factors. Moreover, SOX10 or PAX3 mutant proteins fail to transactivate this promoter, providing further evidence that the two genes act in concert to directly regulate expression of MITF. In situ hybridization experiments carried out in the dominant megacolon (Dom) mouse, confirmed that SOX10 dysfunction impairs Mitf expression as well as melanocytic development and survival. These experiments, which demonstrate an interaction between three of the genes that are altered in WS, could explain the auditory-pigmentary symptoms of this disease.
UnivIS-Import:2015-03-05:Pub.2000.med.IB.LPCIPDBI.intera